Psychoanalysis and Repetition: Why Do We Keep Making the Same Mistakes? - Nasio, Juan-David (State University of New York Press, 2019)
In Psychoanalysis and Repetition, Juan-David Nasio, one of the leading contemporary Lacanian psychoanalysts in France, argues that unconcious repetition represents the core of psychoanalysis as well as no less than the fundamental constitution of the human being–back cover.
Keywords: Lacan; Jacques; 1901-1981; Psychoanalysis; Repetition (Philosophy); dept.phi; faculty_collection

Heidegger and Practical Philosophy - Raffoul, François; Pettigrew, David (State University of New York Press, 2002)
Investigating the extent to which Heidegger's thought can be read as a crucial resource for practical philosophy and the articulation of an ethos for our time, leading scholars offer a sustained and intensive focus on Heidegger's thought of praxis.–(Source of description unspecified.)
Keywords: Heidegger; Martin; 1889-1976; Ethics; Political science; Philosophy; Practice (Philosophy); dept.phi; faculty_collection

Heidegger in France - Janicaud, Dominique (Indiana University Press, 2015)
Dominique Janicaud claimed that every French intellectual movement–from existentialism to psychoanalysis–was influenced by Martin Heidegger. This translation of Janicaud's landmark work, Heidegger en France, details Heidegger's reception in philosophy and other humanistic and social science disciplines. Interviews with key French thinkers such as Françoise Dastur, Jacques Derrida, Éliane Escoubas, Jean Greisch, Philippe Lacoue-Labarthe, Jean-Luc Marion, and Jean-Luc Nancy are included and provide further reflection on Heidegger's relationship to French philosophy. An intellectual undertaking of authoritative scope, this work furnishes a thorough history of the French reception of Heidegger's thought.–Publisher website.
Keywords: 20th century; Philosophers; France; Heidegger; Martin; 1889-1976; Philosophy; French; Interviews; dept.phi; faculty_collection

French Interpretations of Heidegger: An Exceptional Reception - Pettigrew, David; Raffoul, François (State University of New York Press, 2008)
"French Interpretations of Heidegger undertakes a philosophical engagement with the work of the most significant and creative figures involved in the reception of Heidegger in France. The essays address those thinkers who have been influenced by Heidegger's thought and have interpreted it in remarkable ways, including Levinas, Beaufret, Sartre, Merleau-Ponty, Foucault, Derrida, Deleuze, Nancy, Lacoue-Labarthe, Irigaray, Zarader, Greisch, and Dastur. The volume explores the extraordinary impact that Heidegger's thought has had on contemporary French philosophy, including such movements as existentialism, deconstruction, feminist theory, post-structuralism, and hermeneutics, and illustrates its impact on the American continental scene as well."–Jacket.
Keywords: Heidegger; Martin; 1889-1976; Philosophy; French; dept.phi; faculty_collection

The suppression of cultural memory and identity in Bosnia and Herzegovina - Pettigrew, David (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter identifies an orchestrated effort in “Republika Srpska”—an entity within Bosnia and Herzegovina that was recognized by the 1995 Dayton Peace Agreement − that is designed to prevent survivors of the genocide from erecting memorials to the victims in such locations as Višegrad, Prijedor, and Foča. While memorials for victims have been prohibited, and survivors have been prevented from using the term “genocide,” memorials to the perpetrators have been installed in the center of Višegrad, and near the Trnopolje concentration camp in Prijedor Municipality. In the hills above Sarajevo, in a location from which the city’s residents were attacked during the siege, a plaque honoring indicted war criminal Ratko Mladić has been installed. Accordingly, this chapter considers the extent to which the discriminatory practices regarding memorials in Republika Srpska constitute a violation of human rights. Further, the chapter argues that, following Raphael Lemkin’s definition of genocide, the prohibitive policies in Republika Srpska with respect to memorials and commemorative practices constitute nothing less than a continuation of the genocide, a second phase of the genocide designed to ensure the permanent erasure of a world that was destroyed. These human rights violations and the continuation of the genocide are a troubling testament to the failure of the international community in Bosnia, and to the problematic legacy of the Dayton Peace Agreement.
tex.ids: lens.org/044-520-161-353-25X, pettigrewSuppressionCulturalMemory2018a
Keywords: Apartheid; Cultural memory; Dayton Peace Agreement; Dayton peace agreement; Health Psychology; Health psychology; History of World War II and the Holocaust; Human rights; Prohibited memorials; Public Health; Public health; Raphael Lemkin; Sociology; Sociology; general; World War; 1939-1945; dept.phi

The Creation of the World, or, Globalization - Nancy, Jean-Luc (State University of New York Press, 2007)
"Appearing in English for the first time, Jean-Luc Nancy's 2002 book reflects on globalization and its impact on our being-in-the-world. Developing a contrast in the French language between two terms that are usually synonymous, or that are used interchangeably, namely globalisation (globalization) and mondialisation (world-forming), Nancy undertakes a rethinking of what "world-forming" might mean. At stake in this distinction is for him nothing less than two possible destinies of our humanity, and of our time. This book is an important contribution by Nancy to a philosophical reflection on the phenomenon of globalization and a further development on his earlier works on our being-in-common, justice, and a-theological existence."–Jacket.
Keywords: Globalization; Philosophy; Political science; Philosophy; Teleology; dept.phi; faculty_collection